Everyday life in the Near East: the evidence of the 7th/13th-century illustrations of Al-Hariri's Maqamat - Guthrie, Shirley (The University of Edinburgh, 1991)
Six 7th /13th -century illustrated manuscripts of al- Harirî's Magámát are the subject of this thesis. The Magámat or "Assemblies" are justly viewed, after the Qur'an itself, as "the chief treasure of the Arabic tongue ". There is a terminus ad quern of 1310 for the London B.L. or. 9718 manuscript, because its artist /scribe lived to eighty years of age, and the possibility exists that it properly belongs to the second half of the 7th /13th century. This is an interesting manuscript; unfortunately, its poor state precludes detailed study.

The Maq mát comprise 50 tales of a gifted hero, .Abú Zayd, who delights in duping his fellow men from all walks of life and in a variety of lands by masterly displays of erudition; they occur in the lawcourt, the governor's palace, the bustling süq, the mosque, the city or in more rustic surroundings. It is proposed that the illustrations offer an unparalleled insight into the life of the period.

Some 100 photographic reproductions from the 7th /13th- century manuscripts are included, the majority of them in colour. Individual illustrations appear in the body of the thesis, with a translation of the surrounding text in bold typeface; a further selection of miniatures is interspersed in the catalogues. The main reason for their choice was the desire to give as varied a selection as possible, and to reflect the actual material of the thesis.

For example, the Paris B.N. arabe 5847, Leningrad Academy of Science S.23 and Istanbul Suleyrnaniye Mosque Esad Efendi 2916 manuscripts all yielded valuable evidence concerning architectural and landscape settings and inherited iconographies; Paris B.N. arabe 3929, with Paris B.N. arabe 5847, {the Wásiti manuscript} demonstrated masterly psychological insight into the characters on the part of the artist; the painterly and decorative aspects of Paris BoNL arabe 6094 were revealing and provided an alternative to one's notions of an 'Arab' manuscript, while the London B.L. or 1200, although a fairly literal and in some respects inferior work, was nevertheless of value as the reflection of an existing tradition.

Other factors, such as satire or visual pun, were also considered, but the final choice was necessarily circumscribed by the chapter headings; these in turn cover as broad a spectrum of everyday life as possible. One can hardly claim to produce a fully comprehensive selection from some four hundred and fifty illustrations, but this thesis is an attempt to visualise the contemporary scene through the eyes of the author, the narrator and the painter. It should be borne in mind that al-- Hariri was writing some one hundred years before the Magámát manuscripts were illustrated.

Visual evidence is reinforced with reference to contemporary manuscript illumination and illustration, and the fields of the decorative arts and architecture, This material is further amplified by literary references, which include belles lettres {adab }, historical accounts, poetry and anecdotal works.

My initial approach was sociological. I wished to look at these paintings not as documents of style or iconography, as is so often the method followed by Western art historians, but to examine them as visual evidence amplifying and complementing literary and historical accounts of the mediaeval Near East. The aim is that the thesis should provoke, and stimulate a wider interest in the illustrated Magämát.